"Oh, you've got such a strong accent": Language Identity Intersecting with Professional Identity in the Human Services in Australia. (29th November 2012) - Harrison, Gai
Abstract: Language operates as a form of differentially valued cultural capital that is an influential factor in educational and employment outcomes. English in particular represents a valuable form of linguistic capital in both the broader world market and many regional and local contexts. This article, focusing on one group of professionals, draws on an exploratory study carried out with overseas‐born bilingual social workers residing in Australia, who reflect on how their language identities intersect with their professional identities in the human services workplace. Although most informants identified tangible benefits associated with being bilingual, especially in terms of working with a diverse clientele, they were equally aware of how being categorized as a 'non‐native' speaker of English could diminish their professional credibility and thwart their chances of upward mobility in the workplace. In this regard, this article highlights inconsistencies in how difference is valued in the human services workplace, implicating a more covert process of linguistic othering.